Generation of brown gas from a dry cell HHO generator using chemical decomposition reaction. Issue 1 (April 2021) - Sivakumar, B; Navakrishnan, S; Cibi, MR; Senthil, R
Abstract: Pollution is a factor that makes humans lives worse; because of this pollution, so much of health hazards are uprising. This article mainly contributes to constructing a dry hydroxy cell generator that generates brown gas, which is usually known as hydroxy gas. The primary catalyst used is lye (NaOH) and caustic potash (KOH), which is to be incorporated with stainless steel and followed by supplying a unidirectional current. The reaction is accelerated since the catalyst offers a proxy pathway to expedite the response. The law of electrolysis of faraday governs this process. To lower the consumption of fossil fuel, which is the primary root cause of pollution. This dissertation provides detailed scrutiny on brown gas generators and its best harvest, which is known to be the highest production volume of HHO gas. This journal deals with how the change in the catalyst, power rating and concentration ratio affects the brown gas production and how NaOH differs from KOH in HHO gas production. The average time taken to produce 1 litre of HHO gas using NaOH is about 53 seconds, whereas it is about 80 seconds for KOH.